FPGA-based PWM for three-phase SEPIC rectifier - Raihan, S.R.S.; Rahim, N.A. (IEICE-Inst Electronics Information Communications Eng, 2010)
This paper presents the design and implementation of synchronous pulse-width modulation (PWM) for a three-phase three-switch Single Ended Primary Inductance Converter (SEPIC). The PWM switching patterns are generated from an Altera Cyclone II field programmable gate array (FPGA) device. Two types of carrier waveforms are used with two 60 degrees sine waveforms, taking less space in the FPGA, providing more space for control circuits. Comparative study of two PWM methods is also shown. Verification of simulation results are based on hardware-in-the-loop technique, to show the effectiveness of digital-based PWM control.